Bronze Age myths? : Volcanic activity and human response in the Mediterranean and North Atlantic regions - Buckland, Paul C.
A first rule of statistics is that the existence of a correlation does not itself prove a causal connection. This is the heart of the recurrent question in later European prehistory Ñ whether in the Mediterranean or in the Atlantic northwest Ñ about volcanic eruptions, their impact on climate, and then of the climatic impact on human populations. The burial under tephra of the Late Bronze Age settlement of Santorini is proof of a particular catastrophe: but is there the evidence to prove wider European calamity?